Proof: Write Stmt Control Map At Unchanged 23
Let's prove the following theorem:
if the following are true:
- the line at time 23 = 2
- the tab at time 23 = 1
- statement at line 2, tab 1 =
z = __add__(x, 3)
- Control Map at time 23 = [ entry 0: (pair ("function", "add_three")), [ ] ]
then Control Map at time 24 = [ entry 0: (pair ("function", "add_three")), [ ] ]
Proof:
Given
1 | the line at time 23 = 2 |
---|---|
2 | the tab at time 23 = 1 |
3 | statement at line 2, tab 1 = z = __add__(x, 3) |
4 | Control Map at time 23 = [ entry 0: (pair ("function", "add_three")), [ ] ] |
# | Claim | Reason |
---|---|---|
1 | Control Map at time (23 + 1) = Control Map at time 23 | if the line at time 23 = 2 and the tab at time 23 = 1 and statement at line 2, tab 1 = z = __add__(x, 3) , then Control Map at time (23 + 1) = Control Map at time 23 |
2 | Control Map at time (23 + 1) = [ entry 0: (pair ("function", "add_three")), [ ] ] | if Control Map at time (23 + 1) = Control Map at time 23 and Control Map at time 23 = [ entry 0: (pair ("function", "add_three")), [ ] ], then Control Map at time (23 + 1) = [ entry 0: (pair ("function", "add_three")), [ ] ] |
3 | 23 + 1 = 24 | 23 + 1 = 24 |
4 | Control Map at time (23 + 1) = Control Map at time 24 | if 23 + 1 = 24, then Control Map at time (23 + 1) = Control Map at time 24 |
5 | Control Map at time 24 = [ entry 0: (pair ("function", "add_three")), [ ] ] | if Control Map at time (23 + 1) = Control Map at time 24 and Control Map at time (23 + 1) = [ entry 0: (pair ("function", "add_three")), [ ] ], then Control Map at time 24 = [ entry 0: (pair ("function", "add_three")), [ ] ] |
Comments
Please log in to add comments